Media’s Framing of The Richard Huckle Case: Unveiling Media Portrayals of Sexual Violence in Malaysia - wilson, Sharon; Lim, Shiang Shiang; Yap, Hui Shan (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
Media coverage plays a dual role in society, as it can both inform and reinforce stigmatizing attitudes on particular issues or situations. Our findings suggest that even negative media coverage could have some advantages, particularly compared to no coverage at all, as it might increase awareness of sexual violence amongst members of society. Anchoring on the case of Richard Huckle, a British pedophile who was arrested and convicted of sexually abusing children in Malaysia, the current study used content and textual analysis to analyse and examine the media coverage of Huckle’s stories (n=64) published in The Star and Malay Mail from 2016 to 2022. Using framing theory, the researchers identified the awareness for the public frame as the most frequently used, followed by methods in prevention, initiator or offender, death of the offender, judiciary and victim's story, which is the least news frame utilised in Richard Huckle’s case articles. The study also determined the news settings and frequency that both Malaysian newspapers used in reporting the case of Huckle and examined the extent of the media in dramatising the portrayal of the case. The authors elaborated using Goffman's dramaturgical approach to help understand that media coverage of pedophilia is not a mere reflection of reality but a constructed narrative whereby it focuses on how social actors such as the offender, victim, police, media are cast into roles, what "performance" the newspaper is staging for its audience and what backstage dynamics (e.g., editorial bias or institutional agendas) may influence the front-stage narrative. By analysing selection, framing, characterisation, contextualisation, and the use of visual and auditory cues, the audience and researchers can better appreciate the complex interplay between media, crime, and societal attitudes.